1996
DOI: 10.1080/02772249609358348
|View full text |Cite
|
Sign up to set email alerts
|

The influences of heavy metals on PAH formation during incineration

Abstract: Previous studies have shown that pollutants from incineration include heavy metal, PAH, PCB, PCDD and PCDF, which pose a threat to human health. It was also shown that most heavy metals were adsorbed on paniculate matter. However, the relations among heavy metals and organic compounds were seldom mentioned. The present study focuses on the relations among particle pollutants, PAH, heavy metals and carbon.The experiments were carried out in a bubbling fluidized bed with two consecutive cyclones, a wet scrubber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Moreover, the presence of heavy metals such as Zn, Cr, Cd, Pb in feed waste has been found to increase the formation of PAHs in solid residues from waste combustion (Wey et al 1996(Wey et al , 2000. Furthermore, it was reported that metallic chlorides CuCl, CuCl 2 (Hatanaka et al 2004;Wang et al 2002), FeCl 3 (Olie et al 1998;Kuzuhara et al 2003) might affect the formation and transformation of PAHs and PCDD/Fs during combustion.…”
Section: Factors Affecting Pahs In Residues From Msw Incinerationmentioning
confidence: 99%
“…Moreover, the presence of heavy metals such as Zn, Cr, Cd, Pb in feed waste has been found to increase the formation of PAHs in solid residues from waste combustion (Wey et al 1996(Wey et al , 2000. Furthermore, it was reported that metallic chlorides CuCl, CuCl 2 (Hatanaka et al 2004;Wang et al 2002), FeCl 3 (Olie et al 1998;Kuzuhara et al 2003) might affect the formation and transformation of PAHs and PCDD/Fs during combustion.…”
Section: Factors Affecting Pahs In Residues From Msw Incinerationmentioning
confidence: 99%
“…When the content of Cd in the feedstock was increased from 0 to 2.0 wt%, the DREs of total PAHs by prepared and commercial V 2 O 5 -WO 3 catalysts were decreased from 64% to −26% and from 72% to −122%, respectively. The results indicated that the presence of heavy metal Cd could poison the catalysts and even promote the formations of PAHs [18].…”
Section: Effects Of Heavy Metals On the Catalystsmentioning
confidence: 99%
“…The feedstock containing heavy metals (Cr, Cd, Pb and Zn) increases the quantity of PAHs in the solid phase (present in fly ash) as well as the gaseous phase. Pb and Cr in fly ash not only provide adsorption sites of PAHs but also provide the activation energy required to form high-ring PAHs by the reaction between PAH precursors and the low-ring PAHs in the gas phase [18][19][20].…”
Section: Introductionmentioning
confidence: 99%